2023
DOI: 10.2337/dc21-1663
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes, Atherosclerosis, and Stenosis by AI

Abstract: OBJECTIVE This study evaluates the relationship between atherosclerotic plaque characteristics (APCs) and angiographic stenosis severity in patients with and without diabetes. Whether APCs differ based on lesion severity and diabetes status is unknown. RESEARCH DESIGN AND METHODS We retrospectively evaluated 303 subjects from the Computed TomogRaphic Evaluation of Atherosclerotic Determinants of Myocardial IsChEmia (CREDENCE)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…103,108 Use CTA, which is currently the best, least-invasive method to accurately visualize the arterial wall, 137 to identify individuals in this age range who have image-evident subclinical atherosclerotic plaques in their coronary arteries. CTA has additional advantages: low radiation dose, inexpensive, visualizes noncalcified (soft) and calcified (hard) plaques, gives information about additional pertinent plaque characteristics [137][138][139] ; the readings are becoming more automated 137,[140][141][142] hence less expensive and more reliable; the contrast agents are safer and given in lower doses; and the test can be used to follow In South Korea, usually radical thyroidectomy followed by lifelong thyroid hormone replacement; about one-third underwent partial thyroidectomy 126 If backed by clinical-trial data, brief induction-phase therapy of intensive plasma apoB lowering and then maintenance-phase therapy (proposed in reference 78 and updated here)…”
Section: "[W]e Ought To Be In a Position To Figure Out Ways To Preven...mentioning
confidence: 99%
“…103,108 Use CTA, which is currently the best, least-invasive method to accurately visualize the arterial wall, 137 to identify individuals in this age range who have image-evident subclinical atherosclerotic plaques in their coronary arteries. CTA has additional advantages: low radiation dose, inexpensive, visualizes noncalcified (soft) and calcified (hard) plaques, gives information about additional pertinent plaque characteristics [137][138][139] ; the readings are becoming more automated 137,[140][141][142] hence less expensive and more reliable; the contrast agents are safer and given in lower doses; and the test can be used to follow In South Korea, usually radical thyroidectomy followed by lifelong thyroid hormone replacement; about one-third underwent partial thyroidectomy 126 If backed by clinical-trial data, brief induction-phase therapy of intensive plasma apoB lowering and then maintenance-phase therapy (proposed in reference 78 and updated here)…”
Section: "[W]e Ought To Be In a Position To Figure Out Ways To Preven...mentioning
confidence: 99%
“…Finally, several reports have demonstrated that polyphenols can actively reduce the undesired consequences of the activation of RAGE, either by interfering with receptor signaling as well as by reducing its expression [147][148][149] 8. Lipid metabolism T2DM has been widely associated with an increased risk for atherosclerotic cardiovascular disease which is closely related to raised plasmatic LDL levels with important oxidative changes, [150] which support diabetic hyperlipidemia and accelerated atherosclerosis, increasing the risk of macrovascular complication and cardiovascular morbidity. Noteworthy, LDL is a highly sensitive molecule to hyperglycemia-induced hyperglycemia damage and modification, making them highly pathogenic and atherogenic [151,152].…”
Section: Polyphenols and Advanced Glycationmentioning
confidence: 99%
“…This program[ 8 , 9 ] provides an overview of disease predictions based on computational intelligence. Available data suggest that neural networks were used for lumen wall evaluation, vessel contour determination, and plaque characterization, optimizing for phase with each vessel segment analysis[ 11 ].…”
Section: Introductionmentioning
confidence: 99%